Modernités de Bouvard et Pécuchet, Borges, Queneau - Jacques Neefs (Flaubert: Revue Critique et Génétique)
Raymond Queneau and Jorge Luis Borges both commented on the modernity of Flaubert’s Bouvard and Pécuchet, in the 1950s, emphasizing the singular relationship between this “novel” and the encyclopedia, and with the issue of knowledge. The two authors inscribe the novel in the great universal literature, from Homer to Pindar, from Dante to Joyce. They did so at a time when Flaubert’s “modernity” was the reference for a profound renewal of critical theory. Each point of view is singular, but both illuminate the truly philosophical and profoundly “sceptical” dimension of the novel.